Faixa de suficiência nutricional de roseira cultivada em ambiente protegido - Oliveira, Hermes de Paula Moreira (2013)
The Ibiapaba Plateau - CE is characterized as an irrigated agropolo that has been used by several groups of entrepreneurs in the industry of flowers to deploy their greenhouses or screened to produce various types of flowers. The rose is a crop of great value in the domestic and external market, thereby generating income for the state. The being studied is in a company that produces cut roses to almost 12 years. There are several varieties with different characteristics and colors. Flower beds and plants were selected randomly and collected leaves, soil in the greenhouse and taken to the laboratory at the Federal University of Ceara. The data were submitted to the Mathematical Chance (ChM), Kenworth Balanced Indexes (IBK) and Diagnosis and Recommendation Integrated System (DRIS) method of foliar analysis to obtain sufficiency range. The correct diagnosis of the nutritional factors that limit crop productivity can lead to appropriate management of soil fertility. The nutrients Cu, B and Zn were limiting production of cutrose of the State of Ceará. The studied methods are suitable for foliar diagnosis in cutrose crop.